The narrative of Arthur Gordon Pym and the abyss of interpretation - Kennedy, J. Gerald 1947- (Twayne u.a., 1995)
In this new study of Pym J. Gerald Kennedy considers the novel in light of the political turbulence and racial unrest prevalent at the time of its publication while examining the divide in criticism between those who see the voyage as a meaningful journey toward illumination and those who see it as an ironic commentary on human self-deception. A skillful and thorough analysis of both Pym and the myriad studies of the work, The Narrative of Arthur Gordon Pym and the Abyss of Interpretation will prove a significant addition to the literature on Poe and his works at both the high school and college levels
Keywords: Poe, Edgar Allan <1809-1849> -- Narrative of Arthur Gordon Pym; Poe, Edgar Allan -- 1809-1849 -- The narrative of Arthur Gordon Pym; Poe, Edgar Allan -- 1809-1849; The narrative of Arthur Gordon Pym of Nantucket (Poe); Sea stories, American -- History and criticism; Whaling in literature